Influence of Ca2+, pH, agar and plant growth regulators in the in vitro propagation of Echinocactus parryi (Engelm) - García-González, Dolores Adilene; Santos-Diaz, María Del Socorro; Flores-Margez, Juan Pedro; Osuna-Ávila, Pedro (REVISTA TERRA LATINOAMERICANA, 2020)
Echinocactus parryi is a threatened and endemic species of the municipality of Juarez, Chihuahua, Mexico that presents important limitations for its propagation. The objective of this study was to evaluate the effect of growth regulators, calcium concentration (Ca2+), environmental pH and gelling concentration in the morphogenetic response of E. parryi. The seeds were germinated in Murashige and Skoog (MS) medium at 25% of the concentration of their salts (¼ MS). Epicotyls were cultured in an inverted position in media with different concentrations of 6-benzylaminopurine (BAP) (0-10 mg L-1), indole-3-acetic acid (AIA) (0-0.5 mg L-1), pH 5.7 and 8, Ca2+ (13.2 µM and 26.4 µM) and agar (7 and 10 g L-1). The highest sprout formation (2.9 sprouts per explant) was obtained in MS medium with 2 mg L-1 of BAP combined with 0.5 mg L-1 of AIA, 13.2 µM of Ca2+, pH 8, and 7 g L-1 of agar, at 120 days of culture. The sprouts were transferred to MS medium with 2,3,5 tri‑iodobenzoic acid (TIBA) (0, 0.5, 1 and 2 mg L-1) to induce root formation. The highest rooting (70.5%) was obtained in medium with 0.5 mg L-1 of TIBA. The survival of the plants was 58% at 5 months. This is the first report that describes the in vitro regeneration of E. parryi and constitutes an important advance for its propagation and conservation.